What should be taken away from (3x2 – 4y2 + 5xy +20) to obtain (– x2 – y2 +6xy +20)?
Attachments:
![](https://hi-static.z-dn.net/files/d49/2b548d4154f5b91b7598129a8f423589.png)
Answers
Answered by
2
Step-by-step explanation:
4x^2-3y^2-xy should be taken away from given number
Answered by
6
Let A be taken away.
∴ (3x2 – 4y2 + 5 xy + 20)-A
= -x2 – y2 + 6xy + 20
⇒ A = (3x2 – 4y2 + 5xy + 20) – (-x22 – y2 + 6xy + 20)
= 3x2 – 4y2 + 5xy + 20 + x2 + y2 – 6xy – 20
= 3x2 + x2 – 4y2 + y2 + 5xy – 6xy + 20 – 20
= 4x2 – 3y2 – xy is required expression.
Similar questions
CBSE BOARD X,
3 months ago
Biology,
3 months ago
Math,
3 months ago
Math,
7 months ago
Math,
1 year ago